Some Epidemiological Study of Cryptosporidium Spp. in Broiler chickens in some areas of Karbala Province - Al-Khayat, Kadhim Kh. K.; Al- Zubaidi, Mohammed Th. S. (The Iraqi Journal of Veterinary Medicine, 2015)
The aim of present study to investigate the prevalence of Cryptosporidium Spp. in broiler chickens in some regions of Karbala province and study the effect of months, sex and age on the prevalence of parasite. The results were indicated that the overall percentage of infection was20.71%. The highest rate of infection in Al-Husseiniya which amounted to 22.41% and the lowest in the Ain Al-Tamur region (18.86%), while the highest rate of infection was in March which amounted to 30% and the least in May month reaching 11.42%, and by age groups was the highest rate of infection at the age of five weeks (28.72%) and the lowest at the age of two weeks (13.18%), and significant difference was recorded between two sex female recorded (33.33%) and male (17.05%).